TMR, MRE, and X-ray photoelectron spectroscopy of Fe-SiO₂ granular films - Kravets, V.G.; Poperenko, L.V.; Vinnichenko, K.L. (Functional Materials, 2005)
Feₓ(Si0₂)₁₋ₓ magnetic granular films below the percolation threshold (х < 0.45) have been studied using tunneling magnetoresistance (TMR), magnetorefractive effect (MRE), and X-ray photoelectron spectroscopy. Maximum magnetoresistance ratio of 3.7 % at room temperature was observed for films of Fe₀.₃₅(Si0₂)₀.₆₅ composition. Both the experimental and theoretical analysis reveal a correlation between TMR and MRE, thus demonstrating the usage possibility of the MRE as a contactless method to measure the TMR. The chemical surface structure was analyzed by X-ray photoelectron spectroscopy (XPS) and compared to that of the corresponding Si0₂ and Fe surfaces. The XPS spectra of Feₓ(Si0₂)₁₋ₓ granular films display two main peaks at 707 and 720 eV, which arise from Fe 2р₃/₂ and Fe 2р₁/₂, respectively, and a small peak appears around 710.5 eV due to Fe₂0₃.